Narrative Landmines : Rumors, Islamist Extremism, and the Struggle for Strategic Influence - Bernardi, Daniel Leonard (Book collections on Project MUSE., 2012)
Narrative Landmines explores how rumors fit into and extend narrative systems and ideologies, particularly in the context of terrorism, counter-terrorism, and extremist insurgencies. Beyond face-to-face communication, this book also addresses the role of new and social media in the creation and spread of rumors. Its concern is to foster a more sophisticated understanding of how oral and digital cultures work alongside economic, diplomatic, and cultural factors that influence the struggles between states and non-state actors in the proverbial battle of hearts and minds. By providing fresh dat.